PENGARUH TEKNOLOGI INFORMASI DALAM PERKEMBANGAN BISNIS - Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2010)
ABSTRACT The development of information technology is rapidly triggered by the need for information quickly, accurately, and current. Information technology has become a major facility for the activities of various sectors of life which contributed greatly to the fundamental changes in organizational management structure and operations, information technology has been exploited by some people who can see business opportunities of the technology, influence and role of information technology indirectly, have made an online business grow. Those who understand the business can see good opportunities in the world of online business. Because many of the benefits or profits in the business online. So, Information Technology (IT) plays an important role in the development of online business information technology or IT has been commonly referred to many an important role in various fields that exist in this world. These areas include communications, medicine, economics and others. Online business is a lot of this outbreak could not be separated from the influence and role of IT. Keywords: Information technology, online business, opportunity.